Antecedents and Consequences of Schema Modes among Adults - HUMAIRA YASMIN (Journal of Peace, Development and Communication, 2021)
The research investigated the mediation of schema modes between emotional maltreatment and personality disorders of adults. The study was conducted with 1000 adults by using cross-sectional survey design. the study was completed in three years from April 2016 to April 2019. Mediation analysis through PROCSS 3.0 was conducted (for testing the hypotheses) which explained that schema modes mediated between emotional maltreatments and personality disorders of adults. Thus the Schema Theory gained support from the empirical data. More specifically, the schema modes mediated for all personality clusters including cluster-A, B and C. In line with these empirical insights, the maladaptive personality traits also mediated between emotional maltreatments and personality disorders of adults. Firstly, these findings enhance the validity of Schema Theory and thus the study has theoretical significance. On the other hand, the findings seek the attention of mental health practitioners to shift their focus from the antecedent / consequence dichotomy to the developmental nature of personality disorders which follows the process of aging and goes through different milestones of lifespan development before the diagnosis of personality disorders at the adult age. The clinical interventions have long been focused on the management of the personality disorders among patients. However, they have little focus on the preventive measure which can be more effective than management. The study has empirically established the fact that the case history of personality disorders stems from the experiences of emotional maltreatment which should be prevented or treated properly. If not treated, theses maltreatments lead towards the construction of early maladaptive cognitive schemas. If these maladaptive schemas are not eradicated through cognitive restructuring, these remain active during the course of aging—if not properly deactivated through cognitive restructuring—and finally appear in the form of personality disorders during early adulthood. Thus the study suggests multiple steps to prevent the development of personality disorders. Keywords: Emotional maltreatment, maladaptive schema modes and personality disorders